Love Has no Age: The Theme of Love in the Three Female Generations of the Brazilian Series 3 Teresas - Góis Dantas, Sílvia (2023)
This article analyzes the verbal-visual discourse about love in the three generations of the series 3 Teresas (Ribeiro, 2013-2014). Through the analysis of the discursiveness of the series, it has been possible to identify the thematic axes on which the generational verbal-visual narrative is structured; this text is limited to the issues related to love and sexuality.